Fantastic Beings and Where to Make Them ‒ Boats as Object-Beings in Bronze Age Rock Art - Fahlander, Fredrik (Current Swedish Archaeology, 2019)
The boat motif in Bronze Age rock art is generally assumed to represent real or symbolic boats in some form. In this paper, however, it is argued that Bronze Age rock art motifs are independent material articulations, made to do something rather than to represent. From such a perspective, the hybrid character of the boat motif as part animal, part object is conceived as a special type of entity, an object-being that has no original elsewhere. The change of perspective, from representation to articulation, and from object to being, allows for a more coherent view of Bronze Age rock art as primarily enacted imagery integrated with rock and metal as vitalist devices, aimed to affect the world.